Using AI in Healthcare to Manage Vaccines Effectively - Muhammad Umer Qayyum; Abdul Mannan Khan Sherani; Murad Khan; Ashish Shiwlani; Hafiz Khawar Hussain (CV. Shofanah Media Berkah, 2024)
With its ability to streamline logistics, provide fair access, overcome logistical obstacles, improve safety and security, and enable real-time monitoring and feedback, artificial intelligence (AI) is completely changing the way vaccines are distributed. AI optimizes transportation routes to guarantee timely delivery, enables tailored interventions to reach marginalized areas, and improves cold chain management to maintain vaccine efficacy. AI also makes it possible to identify and mitigate risks proactively, monitor negative events in real time, and protect against theft and counterfeiting. AI enables stakeholders to make knowledgeable decisions, maximize distribution efforts, and guarantee the efficacy and safety of vaccinations by leveraging data and analytics. AI technology is expected to advance worldwide efforts to attain health parity and safeguard public health as it develops further, making it even more capable of distributing vaccines.